Social environment factors and its relationship with the appreciation of the character of polytechnic students - Shaiffuddin Bin Anuar; Norni Binti Abd Wahab (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
Social environment can influence students’ moral. This study aimed to see the influence and relevance of such relationships. Social environment in this study includes parents, teachers, peers, artists, environmental institutions, communities and discipline enforcement. This quantitative study carried out against 400 student semester one Sultan Mizan Zainal Abidin Polytechnic as samples. Consists of students of Department of Electrical Engineering and Department of Mechanical Engineering. Both departments were chosen because they have student majority. The results show that social environment influential significantly against the formation of students ' moral character. The highest influence of social environment is the parent (M= 4.25, SD = 0.57), followed by teachers (M=3.97, SD = 0.61), society (M=3.81, SD = 0.60), the institutional environment (M= 3.76, SD = 0.59), discipline enforcement (M =3.74, SD = 0.73), peers (M=3.63, SD =0.62) and artists (M=2.80, SD=0.93). The findings contribute to the improvement of teaching and learning activities and development of students ' moral character in the institution as a whole.